Model Komunikasi Ruang Literasi dalam Meningkatkan Minat Baca di Kalangan Mahasiswa UINSU Medan - Salsabila, Adinda; Aulia, Fadlan; Rahmanda, Rafli; Natasha, Putri Aulia; Khairani, Unnaisah (Medan Resource Center, 2022)
Reading is a crucial skill that any student must incorporate into their daily routine. By engaging in reading, you can get new knowledge, and you can increase your level of concern for your social well-being through reading. But at State Islamic University of Nort Sumatera, particularly among the Student, the reading program is rather erratic. Compared to reading a book, student more frequently uses the internet to search for educational information and materials. This suggests that at UINSU, bias is not yet a way of life, and bias among UINSU women is more persistently expressed in their viewing of television programs and dramatic readings on gaming console. Because of this, Literasi room had to reappear in order to provide the student with renewed inspiration to read. It is anticipated that this Literal Component will be an effective solution to address the issue of Minat Baca in the student community.